Literature Review: Measuring Titanium Dioxide Particles Size in Sunscreen and Its Effectiveness as UV Radiation Absorber - Asep Bayu Nandiyanto; Dhea Salsabila; Fakhira Aulia; Fathia Ravi Hafidza; Putri Sayyida Ashfiya; Syifa Salsabila (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The purpose of this study was to use the ICP-MS method to examine the particle size of TiO2 in various forms of sunscreen, with a focus on the effectiveness of UV radiation absorption. Research methods are employed to support this research by reviewing many sources as references. ICP-MS was used to measure the size of TiO2 nanoparticles in sunscreens in various forms such as powder, cream, and spray. The particle size of TiO2 in powder form is 41.17nm, in cream form is 42nm, and in spray form is 94.5nm, according to the studies. Sunscreen in the form of a spray has the biggest particle size in terms of particle size. Absorption and scattering can be increased by using larger particles